Coping with the Consequences of a Housing Crisis During the Great War: The Case of Right-Bank Ukraine in 1914–1918 - Konstantin A. Kholodilin; Tymofiy Gerasymov (International Journal of Regional and Local History, 2019)
The enormous demographic and economic disturbances caused by World War I forced participating governments to drastically restrict market freedoms. In particular, the state began intervening actively in the housing market. For the first time, Ukraine, as a part of the then Russian Empire, implemented rent controls and protection of tenants from eviction. This paper concentrates on interventions in the rental housing market of Right-Bank Ukraine during the war. It identifies the factors triggering intervention in the landlord-tenant relationship; analyses changes in the housing legislation; and assesses the effectiveness of the regulations.
Keywords: 330; Rental housing market; rent controls; tenant protection; government regulations; World War I; Right-Bank Ukraine